(untitled) (Swiss Medical Weekly, 2016)
Recently, the European Society of Cardiology (ESC) and the European Atherosclerosis Society (EAS) published a consensus paper giving guidance on the definition and management of statin-associated muscle symptoms (SAMS), as well as the use of proprotein convertase subtilisin kexin 9 (PCSK9) inhibitors in very high-risk patients. The occurrence of SAMS can have a major negative impact on treatment adherence and, consequently, on the prognosis of cardiovascular diseases. In addition, both the ESC guidelines on the prevention of cardiovascular disease (CVD) in clinical practice with sections addressing global strategies to minimise the burden of CVD at population and individual levels, and the 2016 ESC/EAS guideline for the management of dyslipidaemias, focus on evaluation and treatment of SAMS. The release of these guidelines was a source of great interest to clinicians, as new emergent therapies, such as the PCSK9 inhibitors, have been approved for the treatment of dyslipidaemias: recently, both the US Food and Drugs Administration (FDA) and the European Medicines Agency (EMA) approved the use of PCSK9 inhibitors as add-ons for the treatment of hypercholesterolaemia in cases where low-density lipoprotein cholesterol (LDL-C) target levels could not be reached with maximum tolerated statin doses alone, or instead of statins in the event of SAMS. Because of the relatively high cost of these new therapies, physicians need to justify the use of PCSK9 inhibitors by demonstrating that their high-risk patients’ LDL-C levels have remained high (1) despite a well-conducted, but insufficiently effective high-intensity statin therapy (e.g. rosuvastatin 10–20 mg or atorvastatin 40–80 mg), or (2) in the event of the patient developing side effects, in particular severe SAMS, during treatment with at least three statins. In addition to SAMS, the use of PCSK9 inhibitors may be considered in patients with documented atherosclerotic cardiovascular disease or in patients with familial hypercholesterolaemia and poorly controlled LDL-C under the combination of maximum tolerated stain and ezetimibe.